Role Play as a Methodological Strategy to Develop Socio-emotional Skills in University Students - Palacios Garay, Jessica Paola (2022)
Emotions and education are closely related, since adequate emotional management is required to face academic challenges favorably. Socio-emotional skills are personal resources for effectively managing personal and social change and coping with difficult emotions. The objective was to determine the influence of role-playing as a methodological strategy in the development of socio-emotional skills in university students.The study had a quantitative approach, applied type, with an experimental, quasi-experimental design. The sample consisted of 252 students from the Faculty of Health of a fifth-cycle private university. Information collection was carried out through the revised version of the social skills scale composed of six dimensions. The results showed that the role-playing program develops socioemotional skills due to U-Mann-Whitney =.000 and z= -13.725. It is concluded that the role-play strategy helps to address a tension-free environment, enhancing the personal and interpersonal skills of university students.